Komunikasi Organisasi dalam Pengambilan Kebijakan di DPMPTS Kota Tangerang - Jamaludin, Abdul Rafi; Mirza, Mochammad; Alamsyah, Alamsyah; Suseno, Ari (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to explore the relationship between organizational communication and policy making at the Tangerang City DPMPTSP Secretariat. The research background arises from the important role of communication in forming effective decisions and policies in public service organizations. The main objective is to analyze how the dynamics of organizational communication influence the quality of policies and the implementation process at the DPMPTSP Secretariat. The research method used is a qualitative approach using in-depth interviews with leaders, staff and related external stakeholders. Theme analysis was used to organize and interpret the data. The research results show that the quality of organizational communication greatly influences the effectiveness of policy making and its implementation. The findings of this research highlight the importance of clarity of organizational vision and goals, open communication between leadership and staff, and horizontal coordination between units. The implication of this research is the need to strengthen organizational communication as a strategy to improve the quality of policies and be responsive to community needs.